Determinants of MSME Sales Performance: Evidence from E-Commerce and E-Payment Adoption in Rappocini District, Makassar City - Bakri, Rasyidah; Viantika, Ni Made; Ramadhan, Andi Muh Rayhan; Rukka, Rusli M.; Hardiyanti, Siti (Hasanuddin University, 2025)
The rapid development of digital technologies has encouraged e-commerce and e-payment adoption among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Despite their contribution to the national economy, studies examining digital transaction technologies' effectiveness on MSME sales performance locally remain limited. This study analyzes the effects of e-commerce and e-payment adoption on MSME sales in Rappocini District, Makassar City. A quantitative approach used primary data from structured questionnaires of 30 MSME actors selected via purposive sampling. The data were analyzed using multiple linear regression with SPSS. Results show e-commerce adoption has a positive significant effect on MSME sales (β > 0; p < 0.05), as does e-payment usage (β > 0; p < 0.05). Simultaneously, both variables significantly influence sales performance. These findings suggest that strengthening digital platforms and cashless payment systems can enhance MSME sales. Policy interventions should focus on improving digital literacy, infrastructure, and access to digital financial services to accelerate MSME digital transformation.